Pengaruh Perendaman Resin Akrilik Heat-Cured dalam Tablet Effervescent Edamame (Glycine max L. Merrill) sebagai Pembersih Gigi Tiruan Lepasan terhadap Kekasaran Permukaan - Diva Rana Syahirah (Fakultas Kedokteran Gigi, 2025)
The cleanliness of acrylic removable dentures is a common problem for denture users. If not maintained properly, they can cause various issues in the oral cavity. The edamame plant (Glycine max L. Merrill) has the potential to be used as an alternative herbal denture cleaner with minimal side effects on surface roughness and the ability to inhibit microorganisms, which are causative agents for inflammation of the oral mucosa, which is also optimal. This study aims to analyze the effect of soaking heat-cured acrylic resin in edamame effervescent tablets as a removable denture cleaner on surface roughness. Method: The type of research used is experimental laboratory research with a post-test only control group design. The samples were heat-cured acrylic resin plates measuring 65x10x2.5mm, with a total of 30 samples divided into three groups: the immersion group in sterile distilled water solution, the immersion group in commercial effervescent tablet solution, and the immersion group in edamame effervescent tablet solution. Soaking was carried out for 16 days, and the soaking solution was changed every 24 hours. The data results were analyzed using the One-Way ANOVA test and continued with the post-hoc LSD test. Results: There was a significant difference
Reaploud Repository February_Hasyim
Keywords: edamame effervescent tablets; surface roughness; fermentation; heat cured acrylic resin.